Assessment of the Uncertainty for the Spatial Distribution of Lightning Discharge Density Based on the Smoothed Bootstrap Procedure and WWLLN Data: a Case Study - Belikova M. Yu. Marina Yurjevna; Baranovskiy N. V. Nikolay Viktorovich; Karanin A. V. Andrey Vladimirovich; Karanina S. Yu. Svetlana Yurjevna; Skrypnik A. N. Artem Nikolaevich (2022, 2022)
Title screen